Fibromatosis of the maxillary sinus and muscles of mastication; a case report. (Update Dental College Journal, 2014)
Fibromatosis is a rare and locally aggressive benign tumour arising from the musculoaponeurotic structures of the whole body. Although it may occur in oral and maxillofacial region, is extremely rare in the paranasal sinus and involving the muscles of mastication. A 26 years old Bangladeshi male presented with severe trismus will be reported here to focus attention on this rare disease. Post operative histopathology confirmed the disease as fibromatosis. DOI: http://dx.doi.org/10.3329/updcj.v3i2.18000 Update Dent. Coll. j: 2013; 3 (2): 48-54